2014
DOI: 10.5897/jphe2013.0590
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of obesity indicies and blood pressure among non obese adults in Zaria, Northern Nigeria

Abstract: Epidemiological studies from different populations have reported significant association between different anthropometric indicators and hypertension in obese adults but few data are available for the non obese adults of this study population. This study assessed the association between adiposity measures and hypertension risk and analyzed various anthropometric indices (body mass index (BMI), waist-height ratio, waist-hip ratio, waist and hip circumferences) as predictors of hypertension among non obese adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Several studies (Dalton et al, 2003; Gus et al 2004; Sutradhar & Choudhuri, 2017; Wang et al, 2002) reported that the WC, HC and BMI, one or other, were correlated with both SBP and DBP, as found in our study. Our study showed a significant positive association between WC, HC and BMI with MAP as reported by others (Kundu et al, 2017; Sharaye et al, 2014). While considering PP, the present study resembles with another study among Gujrati Indian adolescents found positive association of PP with both BMI and WC (Shaikh et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Several studies (Dalton et al, 2003; Gus et al 2004; Sutradhar & Choudhuri, 2017; Wang et al, 2002) reported that the WC, HC and BMI, one or other, were correlated with both SBP and DBP, as found in our study. Our study showed a significant positive association between WC, HC and BMI with MAP as reported by others (Kundu et al, 2017; Sharaye et al, 2014). While considering PP, the present study resembles with another study among Gujrati Indian adolescents found positive association of PP with both BMI and WC (Shaikh et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…In this study WC, WHR and WHtR measurement was positively correlated with SBP and DBP in men and with DBP in women. In their study Sharaye and colleagues 31 found significant associations between WHtR and SBP and DBP in both men and women, and with WC and SBP in men only. 31 Some 51% of the study sample was classified as being hypertensive (BP ≥ 140/90 mmHg).…”
Section: Discussionmentioning
confidence: 87%
“…In their study Sharaye and colleagues 31 found significant associations between WHtR and SBP and DBP in both men and women, and with WC and SBP in men only. 31 Some 51% of the study sample was classified as being hypertensive (BP ≥ 140/90 mmHg). These findings corroborate a statement issued by the Heart and Stroke Foundation of South Africa (HSFSA) of a high prevalence of hypertension in South Africa.…”
Section: Discussionmentioning
confidence: 87%